Evaluation of E-Learning Website Quality of Universitas Islam Majapahit Using Webqual 4.0 and IPA - Nur Diniyanti; Anita Wulansari; Rafika Rahmawati (bit-Tech, 2025)
The rapid development of digital technology in education requires higher education institutions to provide online learning systems that are effective, responsive, and user-oriented. The e-learning website of Universitas Islam Majapahit (UNIM) serves as the main platform supporting student learning activities, yet issues remain regarding response speed, information availability, and interface design. This study aims to evaluate the quality of UNIM’s e-learning website using the WebQual 4.0 model, modified by adding the User Interface Quality variable, and analyzed with the Importance Performance Analysis (IPA) method. Data were collected through a five-point Likert scale questionnaire involving 281 screened respondents. The findings indicate an average conformity level of 95%, yet several indicators reveal negative gap values, reflecting performance that has not met user expectations. Six indicators SIQ1, SIQ2, SIQ3, SIQ4, SIQ5, and UIQ2 were identified in Quadrant I, marking them as top priorities for improvement. The implications of this study highlight the need to enhance system responsiveness, service interaction quality, and interface usability to meet user expectations. Practically, the results provide guidance for improving the development of UNIM’s e-learning website, while theoretically, this study reinforces the applicability of the modified WebQual 4.0 as a comprehensive evaluation method for assessing the quality of online education services.